2013
DOI: 10.1089/mdr.2012.0086
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics ofStaphylococcus aureusSmall Colony Variant and Its Parent Strain Isolated from Chronic Mastitis at a Dairy Farm in Beijing, China

Abstract: Staphylococcus aureus is a major pathogen associated to bovine mastitis and has the ability to form a slow-growing population termed the small colony variants (SCVs). From 20 samples of 5 chronic S. aureus cases, 1 SCV isolate (SCV102) was recovered simultaneously with 1 of 8 S. aureus isolates. SCV102 showed auxotrophy for thymidine and had a slow growth rate. Intracellular persistence in human mammary epithelial cells (HBL100cell line) monolayer revealed that SCV102 isolate had minimal cytopathological effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 45 publications
(69 reference statements)
0
9
0
Order By: Relevance
“…Some S. aureus strains are capable of switching to an alternative Small Colony Variant (SCV) phenotype, allowing their survival under stressful conditions (Proctor et al, 2006; Bui et al, 2015b). S. aureus SCVs have been identified for many decades (Jensen, 1957), but only sparked more research interest in recent years when they were found to be associated with chronic recurrent infections in both humans (Schneider et al, 2008; Maduka-Ezeh et al, 2012; Wolter et al, 2013; Tande et al, 2014; Masoud-Landgraf et al, 2016) and animals (Atalla et al, 2008; Alkasir et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Some S. aureus strains are capable of switching to an alternative Small Colony Variant (SCV) phenotype, allowing their survival under stressful conditions (Proctor et al, 2006; Bui et al, 2015b). S. aureus SCVs have been identified for many decades (Jensen, 1957), but only sparked more research interest in recent years when they were found to be associated with chronic recurrent infections in both humans (Schneider et al, 2008; Maduka-Ezeh et al, 2012; Wolter et al, 2013; Tande et al, 2014; Masoud-Landgraf et al, 2016) and animals (Atalla et al, 2008; Alkasir et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Their colonies are ten times smaller than the parent strain (Atalla et al 2008), nonpigmented, nonhemolytic and resistant to aminoglycosides. They require more than 18 h of incubation to be coagulase-positive (Attala et al 2008;Attala et al 2011;Alkasir et al 2013). Their small size on tryptic soy or Mueller-Hinton agar is often due to auxotrophy for thiamine, menadione or hemin (Proctor et al 1998).…”
Section: Small Colony Variantsmentioning
confidence: 99%
“…2011; Alkasir et al . 2013). Their small size on tryptic soy or Mueller–Hinton agar is often due to auxotrophy for thiamine, menadione or hemin (Proctor et al .…”
Section: Introductionmentioning
confidence: 99%
“…The SCV isolate S85 did not revert to the large-colony size, and the small phenotype was maintained after subcultivations and upon defrosting from Ϫ80°C storage. It is well known, conversely, that SCVs in S. aureus usually revert after discontinuation of the hostile conditions (6,7,17).…”
mentioning
confidence: 99%
“…colonization and infections. Nevertheless, it is known that SCVs in S. aureus have an increased ability to survive within nonprofessional phagocytes that then behave as reservoirs for recurrent and chronic diseases and reduce exposure to certain antibiotics (6,7,17). Similarly to S. aureus SCVs, S85 showed decreased colony size and reduced coagulase activity.…”
mentioning
confidence: 99%